2021
DOI: 10.1002/hon.2919
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in primary cutaneous diffuse large B‐cell lymphoma, leg type

Abstract: Primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL, LT) is a rare, aggressive lymphoma characterized by skin involvement predominantly in the lower extremities. Immunochemotherapy with or without involved-site radiation therapy (ISRT) is considered standard front-line therapy. Over-expression of PD-L1/PD-L2 is seen in a high proportion of PCDLBCL, LT cases, but efficacy of immune checkpoint inhibitors (ICI) in relapsed/refractory, PCDLBCL, LT has not been thoroughly studied. We conducted a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…R-CHOP is recognised as the most efficient therapy for PCDLBCL-LT. 1–4 , 7 A French study reported a significant improvement in 3- and 5-year survival rates after treatment with a combination of rituximab and polychemotherapy. 8 …”
Section: Discussionmentioning
confidence: 99%
“…R-CHOP is recognised as the most efficient therapy for PCDLBCL-LT. 1–4 , 7 A French study reported a significant improvement in 3- and 5-year survival rates after treatment with a combination of rituximab and polychemotherapy. 8 …”
Section: Discussionmentioning
confidence: 99%
“…PCDLBCL-LT has an intermediate prognosis, with 5-year disease-specific survival of about 60% and an overall survival of about 50% [ 8 ]. Progression-free survival is about 41.8 months in patients treated with chemotherapy and radiotherapy [ 9 ]. Cutaneous dissemination and relapses are common, and systemic dissemination develops in about 17–47% of cases, mainly to lymph nodes.…”
Section: Primary Cutaneous Diffuse Large B-cell Lymphoma Leg Type (Pc...mentioning
confidence: 99%
“…Cutaneous dissemination and relapses are common, and systemic dissemination develops in about 17–47% of cases, mainly to lymph nodes. Adverse prognostic features include multiple lesions, ulceration, CDKN2A inactivation, and MYC rearrangement [ 8 , 9 , 10 , 11 ]. The prognostic role of MYD88 mutation and bcl2 expression is debated.…”
Section: Primary Cutaneous Diffuse Large B-cell Lymphoma Leg Type (Pc...mentioning
confidence: 99%
See 2 more Smart Citations